Respostas

A melhor resposta!
2014-07-07T17:56:56-03:00
Como resolver (x+3)²=1?

(x+3)² = 1

(x+3)(x+3) = 1
x² + 3x + 3x + 9 = 1
x² + 6x + 9 = 1 --------------igualar a ZERO
X² + 6X  + 9 - 1 = 0
x² + 6x + 8 = 0
a = 1
b = 6
c = 8
Δ = b² - 4ac
Δ = (6)² - 4(1)(8)
Δ = 36 - 32
Δ = 4---------------------------------------√4 = 2
se
Δ > 0
então
x = - b - + 
√Δ/2a

x' = -6 - 
√4/2(1)
x' = -6 - 2 /2
x' = - 8/2
x' = -4

e
x" = - 6 + 
√4/2(1)
x" = - 6 + 2/2
x" = -4/2
x" = - 2

V = {-4: - 2} 
1 5 1
2014-07-07T17:57:42-03:00
(x+3)²=1
(x+3)(x+3)=1
x²+3x+3x+9=1
x²+6x+9=1
x²+6x+9-1=0
x²+6x+8=0

Agora é só fazer baskara:
x=  \frac{- 6 +-  \sqrt{6^{2}- 4*1*8}}{2*1} =  \frac{-6 +- \sqrt{36-32} }{2} = \frac{-6+- \sqrt{4} }{2} = \frac{-6+-2}{2}  \\ x1=-2 \\  x2=-4